2007
DOI: 10.1021/ja077569l
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Okilactomycin

Abstract: A highly convergent synthesis of (-)-okilactomycin is described. Key reactions of this synthesis include a strategy-level diastereoselective oxy-Cope rearrangement/oxidation sequence, a Petasis-Ferrier union/rearrangement tactic, and an efficient RCM reaction to construct the 13-membered macrocyclic ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 50 publications
0
29
0
1
Order By: Relevance
“…20 ) and H-21; and H-9 to H-21 indicated that they were present on the same a-face of the molecule. The NOESY correlations of H-7 to H-5 and H-22 indicated that they were present on the opposite face of the molecule.…”
Section: Structure Elucidationmentioning
confidence: 99%
“…20 ) and H-21; and H-9 to H-21 indicated that they were present on the same a-face of the molecule. The NOESY correlations of H-7 to H-5 and H-22 indicated that they were present on the opposite face of the molecule.…”
Section: Structure Elucidationmentioning
confidence: 99%
“…These synthetic efforts culminated in a total synthesis of unnatural enantiomer (−)‐ 1 a and determination of the absolute configuration of the natural product by Smith et al. in 2007 2d,e. There are no syntheses of chrolactomycin ( 1 b ) reported to date.…”
Section: Methodsmentioning
confidence: 99%
“…5 ) by condensation of a bis-silylated β-hydroxy acid and an aldehyde, ( B ) olefination utilizing either the Petasis5 or Tebbe6 protocol, and ( C ) Lewis acid-promoted rearrangement of the derived enol ether ( 8 ) to yield the 2,6- cis -disubstituted tetrahydropyranone ( 9 ). In addition to the total synthesis of (+)-phorboxazole A, we have also validated this versatile synthetic tactic for the construction of other complex, biologically active natural products, to include (+)-zampanolide ( 10 ),7 (+)-dactylolide ( 11 ),8 (+)-spongistatin 1 ( 12 ),9 (−)-kendomycin ( 13 ),10 (−)-clavosolide A ( 14 )11 and (−)-okilactomycin ( 15 ) 12…”
Section: Introductionmentioning
confidence: 94%